Representation of Coherence in the Story of Ibrahim Peace Be Upon him Based on Discourse Semantics Sign Analysis (Global Journal of Human-Social Science, 2018)
From among the important and old approaches of Quran scholars is thinking about the language and the ways of understanding and interpreting its extensive text that has different artistic, religious, and cognitive aspects. One of these approaches is the linguistic and literary approach to Quran about which many persons such as Seyyed Ghotb, Mostanser Mir, Nil Robinson, Izutsu, Anglika Noyort have compiled a set of plans and books. With advance in the analysis of different issues of linguistics and semiotics in different texts, it might be understood that the text of holy Quran and especially Quranic stories include many of linguistic techniques to convey and induce its sublime concepts. However, this aspect has less been dealt with. By analyzing the story of Ibrahim (peace be upon him) based on discourse semantics signs analysis, the present study tries to investigate and examine different discourse systems such as prescriptive, cognitive-interaction and tension and obtains interesting findings that highlight the elevation of structure and meanings of the story and confirms a body-like unity on the surface and a unique coherence in meaning. Given the point that in this study, the researchers are not to know about the values of Quranic stories for having these discourse systems, but just intend to manifest and highlight this dimension of discourse systems in structure and meaning of Quranic stories.
Keywords: coherence; semantics sign; majesty ibrahim (peace be upon him); greimas